2016
DOI: 10.1002/cbin.10616
|View full text |Cite
|
Sign up to set email alerts
|

High‐mobility group box‐B1 (HMGB1) mediates the hypoxia‐induced mesenchymal transition of osteoblast cells via activating ERK/JNK signaling

Abstract: High-mobility group box 1 (HMGB1) is a nuclear protein that involves the binding with DNA and influences chromatin regulation and transcription. HMGB1 activates monocytes and neutrophils, which are involved in inflammation during wounding. In this study, we investigated the promotion of HMGB1 under hypoxia and determined the regulatory role of HMGB1 on the fibrosis of mouse osteoblast-like MC3T3-E1 cells or of human osteoblast MG-63 cells. Results demonstrated that HMGB1 expression was significantly upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…The mitogen-activated protein kinase (MAPK) signalling pathways, including extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 MAPK, are a series of parallel cascades of serine/threonine kinases that are activated by extracellular HMGB1, which also results in the inflammatory response. It is worth mentioning that these inflammatory molecules, in turn, promote additional release of HMGB-1 from cells, resulting in a vicious cycle [8][9][10][11]. GA, also known as Glycyrrhizin, is a triterpenoid triterpene glycoside that is naturally extracted from the roots of licorice plants.…”
Section: Introductionmentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK) signalling pathways, including extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 MAPK, are a series of parallel cascades of serine/threonine kinases that are activated by extracellular HMGB1, which also results in the inflammatory response. It is worth mentioning that these inflammatory molecules, in turn, promote additional release of HMGB-1 from cells, resulting in a vicious cycle [8][9][10][11]. GA, also known as Glycyrrhizin, is a triterpenoid triterpene glycoside that is naturally extracted from the roots of licorice plants.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Zhang P et al reported that the activated ERK1/2 signaling pathway can elevate the expression of osteogenic genes ( Runx2 , ALP , COL1A1 , and OCN ) to facilitate osteoblast differentiation . More importantly, the transfection with siRNA HMGB1 for 30 or 60 nM has found by Qiu Y and his group to reduced JNK signaling pathways to inhibit cell differentiation and migration in mouse osteoblast‐like MC3T3‐E1 cells which were cultured in α‐MEM supplemented with 10% FBS and with 80 mg/mL enicillin and 80 mg/mL streptomycin . The in‐vitro investigation performed by Lin Feng et al also demonstrated that incubation with 25 ng/mL HMGB‐1 for 5 days can activate ERK signaling pathway to facilitate the secretion of osteoblast‐related genes (ALP and OCN) in MSCs which were cultured in basal culture medium supplemented with FBS, ultimately promoting osteoblast differentiation .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular metabolism associated with cell proliferation, anti-apoptosis, metastasis and resistance is abnormal in tumorigenesis, probably resulting from the regulation of Wnt/β-catenin pathway, mitogen-activated protein kinase signaling pathway and other signaling pathways, and hypoxia has an important role in this process ( 26 , 27 ). It has been reported that hypoxia is also able to maintain the characteristic of cancer stem cells and induce the progression of cancer cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%